Deterministic chaos versus stochastic processes: An empirical study on the Austrian Schilling - US Dollar exchange rate - Jesús Crespo Cuaresma (Institute for Advanced Studies (IHS), 1998)
The classical theory about foreign exchange rate explains its fluctuations as the resulting of a random walk motion. In this paper, such a theory is put into question by performing Brock, Dechert and Scheinkman's (1987) test on the Austrian Schilling - US Dollars exchange rate for the period 1971-1998, giving us strong evidence of nonlinearities in its behaviour. By further analysing, features such as the correlation dimension will be estimated in order to better understand the characteristics of the underlying process.
Keywords: C14; C49; F31; 330; chaos; BDS test; correlation dimension; exchange rate; Chaostheorie; Stochastischer Prozess; Theorie